AI-Based Business Model Analysis of Education-Focused Beauty Salon Entrepreneurship - Putro, Wahyu Sasongko; Dwijuliani, Rina; Rosita, Rosita (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aimed to analyse business models using AI to enhance education in beauty salon entrepreneurship over Surabaya, East Java, Indonesia. Here, the data observation is taken from a famous beauty salon group at Surabaya with three service products such as Make Up, Hair Treatment, and Facial. The daily basis data from customers who use three products was analysed to obtain an estimation value of each service product. In this study, the Artificial Neural Network (ANN) method is performed to find an estimation value with Multi-Layer Perceptron (MLP) architecture with two to three variation hidden layers. The Levenberg-Marquardt backpropagation algorithm is also used to obtain RMSE over training value. The result shows the three products Make Up, Hair Treatment, and Facial were compared by customer basis over famous beauty salon group, Surabaya. Here, The ANN model with four hidden layers MLP architecture with 1000 iterations in the training process. The statistical calculation such as MSE of 172, RMSE of 0.812, MAE of 1.234, and MAPE of 3.123% indicate that the model performs exceptionally well, with minimal errors in predictions, respectively. ANN model is proposed to develop a business intelligence system in the near future in beauty salon entrepreneurship